Valuable Orientations Capture Attention - Laurent, Patryk A. (Vis cogn, 2014)
Visual attention has long been known to be drawn to stimuli that are physically salient or congruent with task-specific goals. Several recent studies have shown that attention is also captured by stimuli that are neither salient nor task-relevant, but that are rendered in a color that has previously been associated with reward. We investigated whether another feature dimension—orientation—can be associated with reward via learning and thereby elicit value-driven attentional capture. In a training phase, participants received a monetary reward for identifying the color of Gabor patches exhibiting one of two target orientations. A subsequent test phase in which no reward was delivered required participants to search for Gabor patches exhibiting one of two spatial frequencies (orientation was now irrelevant to the task). Previously rewarded orientations robustly captured attention. We conclude that reward learning can imbue features other than color—in this case, specific orientations—with persistent value.